Glaciological Investigations of the Bulge and Trunk of Kamb Ice Stream, West Antarctica - Jacobel, Robert (IEDA: US Antarctic Program Data Center, 2009)
Abstract: This data set contains radar data from the Kamb Ice Stream (KIS), formerly known as Ice Stream C, in West Antarctica. The project was part of a larger study to assess the likelihood of ice stream reactivation. Parameters include latitude, longitude, distance along profile, ice thickness pick, bright layer depth, and surface elevation, from approximately 1600 km of ground-based radar traverses recorded during the 2004 and 2005 Antarctic field seasons. Data are available via FTP as ASCII text files (.txt). Profile location maps and sample profile sections are available as Joint Photographic Experts Group (.jpg) image files. The data are also available as binary data on DVD, upon request.